Gamma-Ray assisted synthesis of silver nanoparticles in chitosan solution and the antibacterial properties - Huang, N.M.; Radiman, S.; Lim, H.N.; Khiew, P.S.; Chiu, W.S.; Lee, K.H.; Syahida, A.; Hashim, R.; Chia, C.H. (Elsevier, 2009)
In the present study, chitosan had been utilized as a "green" stabilizing agent for the synthesis of spherical silver nanoparticles in the range of 5-30nm depending on the percentage of chitosan used (0.1, 0.5, 1.0 and 2.0 wt) under gamma-irradiation. X-ray diffractometer identified the nanoparticles as pure silver having face-centered cubic phase. Ultraviolet-visible spectra exhibited the influence of gamma-irradiation total absorbed dose and chitosan concentration on the yield of silver nanoparticles. The antibacterial properties of the silver nanoparticles were tested against Methicillin-resistant Staphylococcus aureus (MRSA) (gram-positive) and Aeromonas hydrophila (gram-negative) bacteria. This work provides a simple and "green" method for the synthesis of highly stable silver nanoparticles in aqueous solution with good antibacterial property.